Analysis of bifurcation points of nonlinear resistive circuits by curve tracing method - Ushida, A. (IEEE International Symposium on Circuits and Systems, 2002)
In this paper, we discuss a computational method for obtaining the bifurcation points of nonlinear resistive circuits. There are many kinds of the bifurcation points such as limit point, branch point and isola. At these singular points, the Jacobian matrix becomes singular so that we cannot apply usual numerical techniques such as Newton method to get them. We present here a curve tracing algorithm which can find out the multiple solutions on a solution curve. We also propose a method of calculating the direction of branches at bifurcation points which helps us to trace the solution curves, automatically.< >